(untitled) (The International Journal of Educational Sciences and Arts, 2024)
The study aimed to identify the motives of the Saudi public to use the official government websites and accounts of the Kingdom of Saudi Arabia on the Internet, as well as to identify the nature of the satisfactions achieved by the public as a result of using these websites and accounts, and to know the relationship between motives and satisfactions using the theory of uses and satisfactions. The study belongs to descriptive studies, and relied on the survey method, and the study sample was a sample of users of government institutions’ websites, males and females, consisting of (100) individuals, in the age group from (18 to 60 years), both males and females, and the questionnaire tool was used as a tool for collecting data. The study reached a set of results, the most important of which are: (The Ministry of Interior website: Absher) came at the forefront of the websites of Saudi government institutions used by the Saudi public, the study sample, with a percentage of (98%), followed in second place by (the electronic portal of the Ministry of Health) with a percentage of (63%), while the website of (Saudi Post Corporation: Sabil) came in third place with a percentage of (49%). It was also shown that (utilitarian motives) came first in the use of the websites of Saudi government institutions by the Saudi audience in the study sample, while (ritual motives) came in second place. Looking at the total average scores of the gratification phrases, it is clear that (content gratifications) came in first place in terms of the gratifications of the Saudi audience as a result of using the websites of government institutions, followed by (communication process gratifications) in second place. The validity of the hypothesis was proven: There is a statistically significant correlation between the motives of the Saudi audience to use the websites of electronic government institutions (utilitarian - ritual), and the gratifications achieved from using those sites (content gratifications - communication process gratifications).